Disaster Education Model for Early Childhood - Juhadi, Juhadi; Budi Nugraha, Satya; Banowati, Eva (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Klaten Regency is one of area in Central Java Province which prone to six kinds of disaster including earthquake, volcano eruption, flood, landslide, fire and hurricanes. The most vulnerable victims of disaster are children. This paper aims to describe the disaster education model for early childhood which applied in a model of playing while learning in the EWS park (Eling/Remember-Waspada/Alert-Siaga/Readiness). It involved government and community, include Regional Agency of Disaster Management (BPBD), Fire Rescue, Search and Rescue Unit, Teachers and Students of Early Childhood. This activity used collaborative participatory approach, which a number of community representatives were involved together in learning and simulating the disaster mitigation. The result of the community service showed that the process of learning activities takes place with a pleasant atmosphere, participants enthusiastically receive any material presented by the instructor. The material consists of flood mitigation, hurricanes, volcanic eruptions and earthquakes. Participants try to practice/simulate using the media provided in EWS Park. Simulations are done in groups and individuals with great enthusiasm.